The mediating role of Shariah compliance in the acceptance of Islamic credit cards: evidence from Malaysia - Al-Shaghdari, Fahd Mohammed Obad; Muhammad, Tijjani; Hashem, Osamah (UIS, 2025)
This study examines the mediating role of Shariah compliance in the acceptance of Islamic credit cards (ICCs) among customers in Malaysia. The primary objective is to assess how customer knowledge, perceived financial cost, and perceived advantage influence the acceptance of ICCs, and whether these relationships are mediated by perceptions of Shariah compliance. A quantitative research approach was adopted, involving the collection of survey data from 220 ICC users. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate both direct and indirect relationships. The empirical findings indicate that perceived advantage and Shariah compliance exert significant direct effects on ICC acceptance, while customer knowledge and financial cost do not exhibit direct statistical significance. Notably, Shariah compliance significantly mediates the relationships between all three independent variables and ICC acceptance. These results emphasize the pivotal role of Shariah compliance in shaping customer acceptance of Islamic financial products. The study contributes to the theoretical discourse on Islamic customer behaviour and offers practical insights for financial institutions aiming to enhance the adoption of Shariahcompliant credit products in Malaysia.